14-3-3ζ negatively regulates mitochondrial biogenesis in GBM residual cells - Jacinth Rajendra (Elsevier, 2021)
Glioblastoma (GBM) is the most lethal primary brain tumour with a median survival of only 15 months. We have previously demonstrated the generation of an in vitro therapy resistance model that captures the residual resistant (RR) disease cells of GBM post-radiation. We also reported the proteomic landscape of parent, residual, and relapse cells using iTRAQ based quantitative proteomics of glioma cells. The proteomics data revealed significant up-regulation (fold change >1.5) of 14-3-3ζ, specifically in GBM RR cells. This was further confirmed by western blots in residual cells generated from GBM cell lines and patient sample-derived short-term primary culture. ShRNA-mediated knockdown of 14-3-3ζ radio-sensitized GBM cells and further stimulated therapy-induced senescence (TIS) and multinucleated giant cells (MNGCs) phenotype in RR cells. Intriguingly, 14-3-3ζ knockdown residual cells also showed a significantly higher number of mitochondria and increased mtDNA content. Indeed, in vitro GST pull-down mass spectrometry analysis of GST tagged 14-3-3ζ from RR cells identified novel interacting partners of 14-3-3ζ involved in cellular metabolism. Taken together, here we identified novel interacting partners of 14-3-3ζ and proposed an unconventional function of 14-3-3ζ as a negative regulator of TIS and mitochondrial biogenesis in residual resistant cells and loss of which also radio-sensitize GBM cells.